(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The integration of Internet of Things (IoT) technologies in agriculture has sparked a revolution, promising to transform the industry’s efficiency, productivity, and sustainability. This article delves into the profound impact of IoT in agriculture, focusing on the utilization of sensors and connectivity. IoT sensors, deployed across farms and agricultural environments, enable real-time data collection and monitoring, offering insights into soil conditions, crop health, weather patterns, and resource usage. The connectivity provided by IoT networks facilitates seamless data transmission and analysis. This synergy empowers farmers with actionable information, optimizing crop management, irrigation, and resource allocation. As a result, the combination of IoT sensors, connectivity, and machine learning is revolutionizing agriculture by providing farmers with real-time data, insights, and decision support tools. This article explores the key applications, benefits, and challenges of IoT in agriculture, painting a comprehensive picture of its transformative potential.